Sistem Pendukung Keputusan Penentuan Badan Usaha Milik Desa Terbaik Menerapkan Metode VIKOR - Muhammad Rizky (STMIK Budi Darma, 2021)
Determining the best BUMDes is not easy, because the decision making for the best or not the best BUMDes is still done manually without using computerization. To do this, it takes a long time and avoids mistakes in determining the best BUMDes, for that we need a decision support system that will help make decisions. The decision support system is a system that can be helpful and easy to use so that decision makers with the best alternatives make decisions in the process of determining the best BUMDes. The VIKOR method is a fairly simple method that can be used in decision making to analyze multi criteria. The VIKOR method is based on ranking and selecting from a set of existing alternatives, it can be used to rank many criteria, both qualitative and quantitative. In the VIKOR method, the best value is the smallest value, not the largest value. The calculation results of this method will be as expected if the selected alternatives meet the predetermined criteria. Thus a decision support system is needed so that it can help make the right decisions in determining the best BUMDes.